Coflowering invasive plants and a congener have neutral effects on fitness components of a rare endemic plant. Issue 9 (20th March 2021) - Larson, Diane L.; Larson, Jennifer L.; Symstad, Amy J.; Buhl, Deborah A.; Portman, Zachary M.
Abstract: Network analyses rarely include fitness components, such as germination, to tie invasive plants to population‐level effects on the natives. We address this limitation in a previously studied network of flower visitors around a suite of native and invasive plants that includes an endemic plant at Badlands National Park, South Dakota, USA. Eriogonum visheri coflowers with two abundant invasive plants, Salsola tragus and Melilotus officinalis, as well as a common congener, E. pauciflorum . Network analyses had suggested strong linkages between E. visheri and S. tragus and E. pauciflorum, with a weaker link to M. officinalis . We measured visitation, pollen deposited on stigmas, achene weight and germination over three field seasons (two for germination) in four populations (two in the final season) of E. visheri and applied in situ pollen treatments to E. visheri, adding pollen from other flowers on the same plant; flowers on other E. visheri plants; S. tragus, M. officinalis, or E. pauciflorum ; open pollination; or excluding pollinators. Insect visitation to E. visheri was not affected by floral abundance of any of the focal species. Most visitors were halictid bees; one of these ( Lasioglossum packeri ) was the only identified species to visit E. visheri all three years. Ninety‐seven percent of pollen on collected E. visheri stigmas was conspecific, but 22% of flowers had >1 grain of E. pauciflorum pollen on stigmas and 7% had >1 grain of S. tragus pollen; <1% of flowers had M. officinalis pollen on stigmas. None of the pollen treatments produced significant differences in weight or germination of E. visheri achenes. We conclude that, in contrast to the results of the network analysis, neither of the invasive species poses a threat, via heterospecific pollen deposition, to pollination of the endemic E. visheri, and that its congener provides alternative pollen resources to its pollinators. Abstract : Eriogonum visheri (Visher's buckwheat) is a rare endemic plant of management concern in the northern Great Plains. Two invasive species, Melilotus officinalis (yellow sweetclover) and Salsola tragus (Russian thistle) and an abundant congener ( E. pauciflorum ; fewflower buckwheat) occur and coflower with E . visheri, suggesting that they might interfere with pollination of the rare species. We found no evidence of pollination interference by either of the invasive species. In addition, evidence suggests that the abundant congener may provide an alternative resource to support pollinators that also visit the rarer species.